The Essex Serpent [compact disc, unabridged] : a novel - Perry, Sarah, 1979- (Harper Audio, 2017)
When Cora Seaborne's brilliant, domineering husband dies, she steps into her new life as a widow with as much relief as sadness: her marriage was not a happy one. Wed at nineteen, this woman of exceptional intelligence and curiosity was ill-suited for the role of society wife. Seeking refuge in fresh air and open space in the wake of the funeral, Cora leaves London for a visit to coastal Essex, accompanied by her inquisitive and obsessive eleven-year old son, Francis, and the boy's nanny, Martha, her fiercely protective friend.